MENGOPTIMALKAN KOMUNITAS MEREK: ANTESEDEN DAN KONSEKUENSI DARI IKATAN PELANGGAN - Oktora P, I Gede Nandya (E-Jurnal Manajemen; Vol 9 No 7 (2020)DO - 10.24843/EJMUNUD.2020.v09.i07.p14, 2020)
This research empirically explain about critical factors in managing brand communities by using qualitative approach. The research analyzes the Critical Success Factors (CSF) of the Harley-Davidson brand community in Indonesia. The respondents taken are key figures in the Harley-Davidson brand community who have contributed to the community. Data is collected through in-depth interviews with semi-structured questions in order to finding the Critical Success Factors (CSF) from the Harley-Davidson brand community in Indonesia. This research finding there are five Critical Success Factors (CSF) that supported the successful implementation of the Harley Davidson brand community strategy in Indonesia. The five Critical Success Factors (CSF) are bonds with brands, social factors, functional factors, entertainment factors, and economic factors. Interestingly, there are two supporting factors that influence the effectiveness of brand community strategies namely products and customers. Keywords : critical success factors (CSF), brand community, loyalty.